2020
DOI: 10.1007/s00259-020-05058-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved oncological outcome after radical prostatectomy in patients staged with 68Ga-PSMA-11 PET: a single-center retrospective cohort comparison

Abstract: Background Positron emission tomography (PET) targeting the prostate-specific membrane antigen (PSMA) has superior sensitivity over conventional imaging (CI) to stage prostate cancer (PCa) and therefore is increasingly used in staging to stratify patients before radical therapy. Whether this improved diagnostic accuracy translates into improved outcome after radical prostatectomy (RPE) has not yet been shown. Therefore, the aim of this study was to compare the oncological outcome after RPE between patients tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…They found that metastasis rate was higher in the high risk group, compared to intermediate risk patients, 19.9% vs. 5.2%, in line with our previous study (17). Recently, Ferraro et al published that PSMA PET significantly improved post-RP outcome comparison to conventional imaging, especially in high-risk PCa patients (25). These results suggest that the impact of PSMA PET is limited in therapy management of intermediate patients, compared to high risk patients.…”
Section: Discussionsupporting
confidence: 81%
“…They found that metastasis rate was higher in the high risk group, compared to intermediate risk patients, 19.9% vs. 5.2%, in line with our previous study (17). Recently, Ferraro et al published that PSMA PET significantly improved post-RP outcome comparison to conventional imaging, especially in high-risk PCa patients (25). These results suggest that the impact of PSMA PET is limited in therapy management of intermediate patients, compared to high risk patients.…”
Section: Discussionsupporting
confidence: 81%
“…The treatment change in the full cohort was 57% after imaging with [ 68 Ga]Ga-PSMA-11 [ 74 ]. In another study, [ 68 Ga]Ga-PSMA-11 could predict the treatment outcome for RP better than conventional imaging, including [ 11 C]choline PET/CT, contrast-enhanced CT, bone scan, or abdominal MRI [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 68 Ga]Ga-PSMA-11 wurde kürzlich von der US-amerikanischen Arzneimittelbehörde FDA zur Diagnostik des Prostatakarzinoms an zwei Kliniken in den USA zugelassen [4], die Überlegenheit von [ 68 Ga]Ga-PSMA-11 gegenüber konventionellen Methoden wurde gezeigt [5][6][7][8]. Die PS-MA-Radioligandentherapie wurde in klinischen Studien er-…”
Section: Hintergrundunclassified